2018
DOI: 10.1111/dom.13458
|View full text |Cite
|
Sign up to set email alerts
|

Changes in obese metabolic phenotypes over time and risk of incident chronic kidney disease

Abstract: MHO subjects are at increased risk for incident CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 56 publications
2
28
0
1
Order By: Relevance
“…As for the MHO related risk factors, cumulative evidence con rmed the association between MHO and renal dysfunction. Some reported that subjects with persistent MHO had 2-fold more increase risk of chronic kidney disease [37], whereas others claimed that metabolic abnormalities, but not obesity caused the mild decrease eGFR [38]. In our study, we found that MHO was associated with higher cumulative incidence of mildly reduced eGFR in both women and men.…”
Section: Discussionsupporting
confidence: 43%
“…As for the MHO related risk factors, cumulative evidence con rmed the association between MHO and renal dysfunction. Some reported that subjects with persistent MHO had 2-fold more increase risk of chronic kidney disease [37], whereas others claimed that metabolic abnormalities, but not obesity caused the mild decrease eGFR [38]. In our study, we found that MHO was associated with higher cumulative incidence of mildly reduced eGFR in both women and men.…”
Section: Discussionsupporting
confidence: 43%
“…Of the excluded studies, 127 were duplicate publications; 177 had irrelevant exposure or outcome; 23 did not divide subjects according to BMI categories and metabolic health status; 4 were review studies; 1 did not use MHNW participants as control group; 1 was a study with overlapped subjects, and 7 were crosssectional reports. The primary eligibility process yielded 8 studies (28,(38)(39)(40)(41)(42)(43)(44) and crosscheck of the references of reviews and included studies, and other databases search yielded 1 additional study (37). Finally, a total of 9 studies, comprising 128773 participants and 4797 incident cases, were included in the quantitative meta-analysis based on the inclusion criteria for CKD risk related to the different phenotypes of body size.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Finally, a total of 9 studies, comprising 128773 participants and 4797 incident cases, were included in the quantitative meta-analysis based on the inclusion criteria for CKD risk related to the different phenotypes of body size. Of these, four were from South Korea (28,37,38,42), one was from Iran (39), two were from China (40,43), one in USA (44) and one was from Japan (41). The sample size of the included studies varied from 1881 to 62249 participants and the follow-up duration ranged from 3.2 to 14 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations